Perbandingan Media Menir Jagung dengan Campuran Serbuk Kayu pada Perbanyakan Bibit F2 Jamur Tiram Putih (Pleorotus Ostreatus) di Kebun Wairita Farm Desa Wairbleler Kecamatan Waigete Kabupaten Sikka - Kayetanus Bura, Laurensius; Hendrikus Darwin Beja; Julianus Jeksen (Pusat riset dan Inovasi Nasional, 2026)
This study aims to 1). Observe and understand the stages of propagating F2 white oyster mushroom seedlings at Wairita Farm. 2). Compare the growth of F2 white oyster mushroom seedlings between corn cobs and a mixture of corn cobs and wood powder. 3). Improve the skills and add to the experience and knowledge of students so that they can apply the knowledge they have gained in the lecture hall. This study used a comparative descriptive experimental approach, which is to compare the growth of F2 white oyster mushroom (Pleurotus ostreatus) seedlings on two different types of seedling media. This research was conducted at the Wairita Farm in Wairbleler Village, Waigete District, Sikka Regency, East Nusa Tenggara Province, over a period of 7 days (Monday to Sunday) during working hours from 08:00 to 16:30 with a break from 11:30 to 14:00. This location was chosen because it is an agricultural business unit engaged in the cultivation of white oyster mushrooms (Pleurotus ostreatus). The study period was 3 months, from September 17 to November 17, 2025. Independent variables and dependent variables. Data were obtained through direct observation of mycelium growth, daily recording during the incubation period, and visual documentation. The results of this study indicate that the success of white oyster mushroom F2 seedling propagation is greatly influenced by the suitability of the medium to the physiological and ecological characteristics of the mushroom. A mixture of corn bran and wood powder proved to be more suitable and is recommended for use in the propagation of F2 white oyster mushroom seeds compared to pure corn bran media.